Ensino da física e senso comum: as idéias prévias dos alunos do ensino médio e a aprendizagem de física - Souza Júnior, Jonas Pereira de (2006)
In this paper the author investigates the presence of spontaneous conceptions of students about the physical phenomena in the educational practice of teachers of high school physics. Addresses changes in teaching strategies the teacher in front of the insertion of spontaneous conceptions in physics classes, pointing out aspects like interest, motivation, classroom dynamics and student as the subject of their own knowledge. The empirical part of the research was developed with three physics teachers and eighty students from the first grade of secondary education at a state technical college of the State Center of Technological Education "Paula Souza" in Mogi das Cruzes, in Greater São Paulo. The methodology for data collection, we used Participant Observation and questionnaires. The research presents alternatives for developing the relationship between the prior knowledge that students bring to the classroom and scientific knowledge. It also shows that the use of knowledge as a subsidy to education changes the quality of performance and student learning.